Salivary defense system alters in vegetarian - Nour Amirmozafari; Houra Pourghafar; Reyhaneh Sariri (Journal of Oral Biology and Craniofacial Research)
Purpose: The aim of this research was investigating antimicrobial and enzymatic antioxidant activities in salivary fluids of vegetarians as compared to normal subjects. Material & Methods: Antimicrobial activity of the saliva samples was evaluated against four clinically important bacteria. The biological activities of three of the main antioxidant enzymes of saliva were measured using appropriate methods of enzyme assay in both groups. Results: According to the results, saliva obtained from vegetarians showed a reduced inhibitory effect on growth of Staphylococcus aureus, Klebsiella oxytoca, Pseudomonas aeruginosa and Escherichia coli as compared to those obtained from the non-vegetarian subjects. The activity of salivary peroxidase, catalase and superoxide dismutase showed a statistically marked decrease in vegetarian group. Conclusions: According to our literature survey, this is the first report on the antibacterial and antioxidant capacity in saliva of vegetarians. Results obtained from the present study have opened a new line of research with the basis of saliva as a research tool.